Implementasi Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga di Kota Batam - Emilda Firdaus (Fakultas Hukum Universitas Islam Indonesia, 2014)
The Law on Domestic Violence Eradication (UU PKDRT) is a government policy to protect the women rights. Up to recent the women of the domestic violence victims are shackled by an incorrect comprehension on religion and culture.This research studies the implementation of UU PKDRT in Batam City, the obstacles, and the preventive attempts. The research used sociological juridical by employing primary data. The result concludes that: first, the implementation of in Batam City is not yet maximum due to the lack of gender sensitivity of both the society and government of Batam; second, the obstacles of the implementation of UU PKDRT lays on the social cultural factor, in which the patriarchal culture still dominates the conventional mindset of the society and many of Batam people do not know UU PKDRT; and third, the attempts taken by the Batam government are through media campaign, socialization of UU PKDRT, and training on the prevention of violence through family education. Besides, the material on understandinggendermust be added in formal schooling to change the old perception existing in our society.